Prevalence and molecular detection of shiga toxin producing Escherichia coli from diarrheic cattle - Akter, MM; Majumder, S; Nazir, KH MNH; Rahman, M (Journal of the Bangladesh Agricultural University, 2016)
Shiga toxin-producing Escherichia coli (STEC) are zoonotically important pathogen which causes hemorrhagic colitis, diarrhea, and hemolytic uremic syndrome in animals and humans. The present study was designed to isolate and identify the STEC from fecal samples of diarrheic cattle. A total of 35 diarrheic fecal samples were collected from Bangladesh Agricultural University (BAU) Veterinary Teaching Hospital. The samples were primarily examined for the detection of E. coli by cultural, morphological and biochemical characteristics, followed by confirmation of the isolates by Polymerase Chain Reaction (PCR) using gene specific primers. Later, the STEC were identified among the isolated E. coli through detection of Stx-1 and Stx-2 genes using duplex PCR. Out of 35 samples, 25 (71.43%) isolates were confirmed to be associated with E. coli, of which only 7 (28%) isolates were shiga toxin producers, and all of them were positive for Stx-1. However, no Stx-2 positive isolate could be detected. From this study, it may be concluded that cattle can act as a reservoir of STEC which may transmit to human or other animals. J. Bangladesh Agril. Univ. 14(1): 63-68, June 2016